Dynamics of social-ecological systems: gender influence in local medical systems - Torres-Avilez, Wendy Marisol; Paulino Albuquerque, Ulysses (Ethnobiology and Conservation, 2017)
Studies have reported that gender influences the variation of knowledge of local medical systems. However, most of the ethnobiological studies that analyze the variation of knowledge have focused on analyzing only the richness of known resources. Therefore, in this review we discuss the importance of analyzing the variation of knowledge between genders with a multifactorial and non-unidirectional perspective. It also presents proposals for future studies that analyze the influence of gender on local medical systems, considering the dynamics of social-ecological systems.